2015
DOI: 10.3389/fnhum.2015.00009
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Variation in the Oxytocin Receptor Gene and Emotional Withdrawal, but not between Oxytocin Pathway Genes and Diagnosis in Psychotic Disorders

Abstract: Social dysfunction is common in patients with psychotic disorders. Oxytocin is a neuropeptide with a central role in social behavior. This study aims to explore the relationship between oxytocin pathway genes and symptoms related to social dysfunction in patients with psychotic disorders. We performed association analyses between four oxytocin pathway genes (OXT, OXTR, AVP, and CD38) and four areas of social behavior-related psychopathology as measured by Positive and Negative Syndrome Scale. For this purpose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 70 publications
4
54
0
1
Order By: Relevance
“…For example, explicit learners of a sensorimotor sequence task exhibited an enhanced ERN relative to implicit learners (Russeler et al 2003). Our results are also consistent with other reports that use of correct vs error feedback differentiates implicit vs. explicit learning tasks (Morrison et al, 2015; Smith et al 2013). Moreover, in the Match tasks, when errors arose in the context of higher behavioral certainty, the ERN was larger and could have reflected a prediction error.…”
Section: Discussionsupporting
confidence: 93%
“…For example, explicit learners of a sensorimotor sequence task exhibited an enhanced ERN relative to implicit learners (Russeler et al 2003). Our results are also consistent with other reports that use of correct vs error feedback differentiates implicit vs. explicit learning tasks (Morrison et al, 2015; Smith et al 2013). Moreover, in the Match tasks, when errors arose in the context of higher behavioral certainty, the ERN was larger and could have reflected a prediction error.…”
Section: Discussionsupporting
confidence: 93%
“…In the light-dark box test, Kmo −/− mice spent significantly less time in the light compartment compared to their wild-type counterparts (Figure 4c) and made a decreased number of entries into the light compartment (Figure 4d). Furthermore, although Kmo −/− mice displayed comparable horizontal, rearing, and center activities as Kmo +/+ mice in a general assessment of locomotion (Supplemental Figure 3), we observed a significant increase in the corner time of the Kmo −/− animals (Time: F (11, 462) =3.50, P<0.001; Genotype: F (1, 42) =7.704, P<0.01; Interaction: F (11, 462) =3.60, P<0.0001; Figure 4e). Together, these data demonstrate increased anxiety-like behaviors in Kmo −/− mice compared to Kmo +/+ mice.…”
Section: Resultsmentioning
confidence: 75%
“…The early response gene (EGR) family is noteworthy for containing several compelling SZ susceptibility genes (39), and studies in forebrain-specific conditional EGR2 mutant mice revealed that EGR2 can act as an inhibitory constraint for certain cognitive functions (40). Arginine vasopressin (AVP) is critical for social interactions (41), its receptor gene is associated with emotional withdrawal, which is frequently observed in persons with SZ (42), and elimination of the AVP gene causes distinct cognitive abnormalities in rats (43). Notably, qPCR analysis did not validate D-amino acid oxidase (DAAO), another DEG associated with SZ pathophysiology (44).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate reliable semantic priming effects in Dutch, English, Finnish and Spanish (for extensive discussions, see Davis & Rastle, 2010; Feldman, O’Connor, & Moscoso del Prado MartĂ­n, 2009; Feldman, Milin, Cho, Moscoso del Prado MartĂ­n, & O’Connor, 2015; Van den Bussche, Van den Noorgate, & Reyn-voet, 2009). For instance, Feldman et al (2015) used a within-experiment manipulation, which included exposing participants to five different SOAs all below 100 ms: they observed shorter latencies to the semantically related conditions in very short SOAs of 34 and 48 ms. Semantic effects also emerged in a cross-case ‘same-different’ task by Duñabeitia, Kinoshita, Carreiras, and Norris (2011). This task requires participants to assess the likeness of a lowercase and an uppercase letter string presented sequentially.…”
Section: Evidence From Masked-priming Researchmentioning
confidence: 82%